(3GdbjSjGJ aj GdMceIs - (3GdOGeGO, eMeO Hf eMeO HGbQ, J (B1041 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdhGMO GdCMO GdUeO GdeUehO CeG HYO aCMhL GdeNdhbjf eMeO Hf eMeO HGbQ OGeGO GdMSjfj jbhd Ef HYV ef de jSYafj Cf (B( ) (3HGdQO ef GdCUMGH SCfdj edJeSG ebJQMG Cf CaQO dg HGdPcQ hgh cJGH af GdLOds
(3BNQgG (B:s
(3Gdaf GdKGdK aj GdadcjGJ Gdadc LSe cQi YQQj dhf GdMeO ddg Ydi EjeGfg hGdUdhI hGdSdGe Ydi MHjHg eMeO Udi Gddg Ydjg hBdg hCUMGHg hCLeYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 48s
(3eYLe GdeDdajf (B3 /630s
(3EjVGM Gdecfhf (B2 / 220s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdadSaI hGdefWbs